FINANCIAL FEASIBILITY STUDY FOR AERIAL INSPECTION SERVICE PROJECT IN INDONESIA - Daryanto, Wiwiek Mardawiyah; Putra, Raymond Angga (International Journal of Psychosocial Rehabilitation, 2020)
In Indonesia, the number of offshore platforms has been growing since the first built in 1969. Nowadays, there are about 613 offshore platforms with various types in Indonesia. It consists of several assets; flare stack, base platform, tower crane, building structure, and telecommunication tower that need to be inspected. As a service company, Applus Velosi introduces a new method for the inspection of offshore platform by using Unmanned Aerial Vehicle (UAV). Since the market of aerial inspection facility for offshore platform is still new, the company have to do a financial feasibility study to organize all necessary details to make a business work, as well as to determine a fair rate for the service charged to the oil and gas company. The objectives of this research were to measure and evaluate the financial feasibility of the project of aerial inspection facility for offshore platform in Indonesia. The research will be anaylzed based on Cost-Volume Profit (CVP) analysis, and financial feasibility analysis which includes break-even analysis, Pay-back Period, Net Present Value (NPV), Internal Rate of Return (IRR), and Weighted Average Cost of Capital (WACC). The project’s tolerance will be analyzed by using sensitivity analysis. The research uses quantitaive methods that can be obtained through through company’s financial data and historical data. This research limitation was only focused on offshore platform of oil and gas industry in Indonesia. The research finding shows that the project of aerial inspection facility for offshore platform in Indonesia is financially feasible using 800 as a base service rate. The project has positive NPV and IRR is higher than WACC, profitability index is greater than 1, and payback period is around 1 year.